PENDIDIKAN BERBASIS ALQURAN: Studi Kasus di Pondok Pesantren Al-Aqobah Jombang - Ulfatun Nisa; Fitriyah Mahdali (LP3M IAI Al-Qolam, 2019)
This study focuses on the interconnection and the integration, namely about the relationship of, education and Alquran. This study is a case study that took Pondok Pesantren Al-Aqobah Diwek Jombang as the research location. There are several arguments that form the basis of this research, firstly, this pesantren is applying both the salafiyah boarding school system and the modern system of education of technology and science. Secondly, santris in this pesantren are required to memorize hadis and Alquran using the principle of one day five verses and one hadis. In a matter of months, santris in this pesantren have studied the science of religion which counts generally should be studied in annual time. This research is a qualitative-explorative study that uses the theory of interconnected-integrative paradigm. In accordance with the research theory, the formulation of the problem taken to conduct this research is “what is the paradigm of Quranic based education and how is it implemented in Pondok Pesantren Al-Aqobah”. The methods of data collection are documentation, observation, and interview. The findings of this study are: (1) Educational and Social Institutions of Pondok Pesantren Al-Aqobah Jombang is an educational institution that offers various programs to develop the potential of santri or students using Alquran as the basis for their education; (2) it uses the MIR (Multiple Intelligence Research) method as an effort to explore various kinds of children's abilities, and so that their potencies can be maximized.